Analisis ko-ekspresi gen-gen regulasi upstream dari gen Dehydrin di tanaman tebu (Saccharum officinarum L.) pada kondisi cekaman kekeringan - Hayati MINARSIH; Jembar PAMBUDI; Riza Arief PUTRANTO (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2020)
Sugarcane plantations in Indonesia have been expanded and shifted to the marginal land characterized by long drought period, therefore, an attempt has been initiated to generate drought tolerance varieties through genetic engineering. It could be conducted by inserting the gene that involve in plant adaptation response to drought stress such as dehydrin (DHN) into sugarcane genome. The promoter of sugarcane DHN gene was isolated and transformed into sugarcane in the previous research. This study aimed to demonstrate the functionality of sugarcane DHN promoter through expression analysis of DHN regulatory genes that play a role in response to drought stress. Expression analyses using RT-qPCR were also conducted on regulatory genes of sugarcane that inserted by Pr-1DHNSo construct treated with drought stress. The results showed that the expressions of SoMYB, SoWRKY, SoNAC, and SoDHN genes were escalated on sugarcane 16 days after stress treatment ranging from 353 to 4067 folds relatively to untreated samples in which SoNAC gene showed the highest expression. On the other hand, the analysis on transgenic sugarcane carrying DHNpromoter construct showed SoNAC and SoDREB expression increased after 72 hours under drought stress. The expression values of SoNAC in transgenic and non-transgenic plants under drought condition were 4.79 and 4.99, respectively. Meanwhile, the expression values of SoDREB in transgenic and non-transgenic plants under drought condition were 13.2 and 13.3, respectively. The results of these experiments showed that the promoter construct of Pr-1DHNSo was induced by drought stress treatments highlighting the regulation of several upstream genes of SoDHN.